Handbook of early childhood development research and its impact on global policy - Rebello Britto, Pia, 1966-; Engle, Patrice L.; Super, Charles M. (Oxford : Oxford University Press, 2013)
'Handbook of Early Childhood Development Research and Its Impact on Global Policy' calls for placing early childhood development at the top of the global policy agenda, enabling children to achieve their full developmental potential and to contribute to equitable economic and social progress worldwide.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Child development -- Research; Child welfare -- International cooperation; Children -- Services for; Children -- Government policy